Pengaruh Pemberian Kombinasi Jus Jambu Biji Merah dan Tomat terhadap Kadar Hemoglobin pada Remaja Putri yang Mendapat Suplementasi Tablet Tambah Darah di SMP Negeri 1 Cihara Tahun 2023 - Wirda Sholihah, Iis; Lulu’ul Badriyah; Ema Huliana W Sitepu (CV. CENDIKIA JENIUS INDONESIA, 2023)
Background : Anemia is a serious global public health problem that mainly affects children and pregnant women. Nutritional anemia is a condition in which the circulating mass of erythrocytes and hemoglobin cannot fulfill its function of providing oxygen to the body's tissues. Objective : Knowing the effect of giving a combination of red guava and tomato juice on hemoglobin levels in young women who received iron supplementation at SMPN 1 Cihara, Lebak Regency in 2023. Method : The research was a quasi-experimental. Using a pretest and posttest design approach with a control group. The subjects of this study were 30 anemic young women. Giving a combination of red guava and tomato juice is given as much as 1 bottle (250 ml) per day for 5 days. Check Hb on the last day using a digital Hb check tool. Data analysis used the t-dependent statistical test. Result : There was an effect of giving a combination of red guava juice and tomatoes on hemoglobin levels before and after the control treatment with a value (p = 0.019) and hemoglobin levels before and after the intervention with a value (p = 0.009) in female adolescents. Conclusion : There was a significant effect of giving a combination of red guava and tomato juice on hemoglobin levels in anemic female adolescents.